3.1k views
19 votes
For f(x) = x+6 and g(x) = 2x + 3, find the following

a. (fog)(x)
b. (g of)(x)
c. (fog)(2)

User Jvnill
by
6.2k points

1 Answer

14 votes

Answer:


(f o g)(x) = 2x + 9


(g o f)(x) = 2x + 15


(f o g)(2) = 11

Explanation:

Given


f(x) = x+6


g(x) = 2x + 3

Solving (a): (f o g)(x)

In functions:


(f o g)(x) = f(g(x))

Solving for f(g(x))


f(x) = x+6


f(g(x)) = 2x + 3 + 6


f(g(x)) = 2x + 9

So:


(f o g)(x) = 2x + 9

Solving (a): (g o f)(x)

In functions:


(g o f)(x) = g(f(x))

Solving for g(f(x))


g(x) = 2x + 3


g(f(x)) = 2(x+6)+3

Open bracket


g(f(x)) = 2x+12+3


g(f(x)) = 2x+15

So:


(g o f)(x) = 2x + 15

Solving (c): (f o g)(2)

In (a):


(f o g)(x) = 2x + 9

Substitute 2 for x


(f o g)(2) = 2*2 + 9


(f o g)(2) = 4 + 9


(f o g)(2) = 11

User Jashim
by
5.3k points